Investigation of Herbal Tea Production from Perilla (Perilla Frutescens) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Perilla is an edible plant and has medicinal properties. The leaves have a very pleasant sweet taste and are used as a spice. Perilla seed and oil are rich sources of phenolic compounds, antioxidants, polyunsaturated fatty acids (α-linolenic acid, linoleic acid, oleic acid, and palmitic acid, omega-3 and omega-6 polyunsaturated fatty acids) and minerals. Perilla is commonly used to flavor the foods. Objective of the present study was focused on the effect of blanching, drying and storage of herbal tea produced from Perilla. Optimal results found that herbal tea would have stable antioxidant capacity while blanching at 95oC in 4 seconds with the presence of 4% CaCl2 submersed in blaching solution; drying at 40oC with 2.0 cm in dimenstion of Perilla; storage under vaccum in PET/AL/PE bag within 6 months without any deterioration.Keywords: Perilla, Herbal tea, Blanching, Drying, Storage, vacuum.